EFIKASI EKSTRAK BIJI JARAK PAGAR MORTALITAS LARVA PENGGULUNG DAUN (Lamposema indicate) PADA TANAMAN KEDELAI (Glycine max) - Chairudin Chairudin; Sumeinika Fitria Lizmah; Rol Mahdi (Universitas Teuku Umar, 2020)
Soybean leaf roller known as Lamposema indicata. These insects attack the leaves of soybean plants by rolling up soybean leaves, that are launched 3-4 weeks after planting. The research aims to find out application of Jathropha curcas extract againts the mortality of soybean leaf roller pest (Lamposema indicata) and reduce damage to soybean plants. This research was conducted in the experimental garden, Faculty of Agriculture, Teuku Umar University in October to November 2019. The research was arranged in a non factorial Completely Randomized Design consisting of 4 levels with 5 replications. The factors experience is Jathropha curcas seed extract concentrate are E1 (control), E1 (20%, E2 (13.3% and E3 (10%). The results shows Lamprosema mortality shows the highest found in the E3 regulation, this is because in the E3 setting it has a high concentration so that the composition of the poisons contained is also high. Castor seed extract (Jatropha curcas) contains the composition of phorbol ester and cursin. Based on the observations displayed during the observation, namely changes in behavior, slowing movement of larvae, discoloration from clear green to pale yellow and compacting of the larva's body cavity.Keywords: Effectiveness of concentration, mortality, leafworm caterpillars